ASPECTS OF MODERNIZATION OF THE INSTITUTIONAL ENVIRONMENT OF INNOVATIVE ACTIVITIES - VYGOVSKYI, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article focuses on the aspects of regional policy for the modernization of the institutional environment of innovation activity at the meso-economic level. The purpose of the article is to substantiate the aspects of modernization of the institutional environment of innovation activity in the regional economy. The essential and content-based characteristics of the institutional environment are generalized. It is established that in the sphere of innovation development this is the most important element of regional economic policy, which occupies a leading position in the conceptual framework of institutionalism theory and modern institutional economics. The author’s definition of the concept of the institutional environment of regional innovation development is provided. The composition of the elements of the institutional environment of regional innovation development is identified. It is determined that in the process of forming the institutional environment of innovation development it is important to focus on two aspects. First, the elimination of shortcomings and gaps within the existing environment; second, the consideration of progressive trends of its modernization. In the case of the economies of Ukrainian regions, such trends include deregulation and neo-institutionalization, formalization of market institutions, reorganization of the management system, and digital transformation of relations. It is proved that their alignment and complementarity make it possible to identify the spectrum of tasks of institutional support for innovation development in the regional economy, namely in the aspects of the basic, system self-regulating, and coordinating role, the expansion of cooperation, and the digitalization of processes and relations.
Keywords: innovations; innovation activity; innovation performance; regional economy; regional policy; institutional environment; modernization